2022
DOI: 10.1108/jfm-03-2022-0023
|View full text |Cite
|
Sign up to set email alerts
|

Impact of project governance on project success, with mediating role of organizational support and project team cohesion

Abstract: Purpose The purpose of this study is to determine how project governance influences project success. According to the authors, such an effect is mediated by organizational support and project team cohesion. The direct and indirect effects of organizational support and project team cohesion provided helpful information. The authors’ objective is to contribute to the project management knowledge of how project team cohesion plays a significant role in project success. Design/methodology/approach Data were coll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 148 publications
1
5
0
Order By: Relevance
“…As indicated in Table 4, the results of governance support the proposed hypothesis 1 (there is a positive relationship between governance and project portfolio success) with a strong positive correlation of r = 0.597 and a significant correlation of p < 0.001. These results confirm observations by other scholars (Irfan & Hassan 2019;Ul Musawir et al 2017;Waseem et al 2022;Young et al 2020). Moreover, the results correspond with the outcome of a similar study that was conducted at the project level (Joslin & Müller 2016).…”
Section: Multiple Correlation Analysissupporting
confidence: 92%
See 1 more Smart Citation
“…As indicated in Table 4, the results of governance support the proposed hypothesis 1 (there is a positive relationship between governance and project portfolio success) with a strong positive correlation of r = 0.597 and a significant correlation of p < 0.001. These results confirm observations by other scholars (Irfan & Hassan 2019;Ul Musawir et al 2017;Waseem et al 2022;Young et al 2020). Moreover, the results correspond with the outcome of a similar study that was conducted at the project level (Joslin & Müller 2016).…”
Section: Multiple Correlation Analysissupporting
confidence: 92%
“…There is a considerable progress in research that examines project governance and its relationship to project success (Irfan & Hassan 2019;Joslin & Müller 2016;Ul Musawir et al 2017;Waseem, Iqbal & Khan 2022;Young et al 2020). However, this advancement has not been made at project portfolio level.…”
Section: Introductionmentioning
confidence: 99%
“…According to Venkatraman (1989), the impact of a predictor variable on a predicted variable is dependent on the fit between a predictor and a moderator variable. For example, Naeem et al (2018) utilised the concept of moderation fit to examine the moderation impact of organisational culture on the relationship between project risk management (predictor variable) and project success (predicted variable). They found that adding organisational culture as a moderator variable weakened the relationship between risk management and project success.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…One way of job creation for developing countries is the ECCs engagement in projects due to the large manual labour force, but the success rate regarding quality, time, cost, and scope is not impressive. Naeem et al (2018) affirmed that construction project success and performance depend on all-inclusive planning from project formation to completion via a project management approach. Many emerging construction contractors, especially in developing countries, lack training and the ability to institute plans to manage business risks (Amoah and Bikitsha, 2021).…”
Section: Introductionmentioning
confidence: 97%